Visible/infrared light-driven high-efficiency CO2 conversion into ethane based on a B–Co synergistic catalyst. Issue 42 (23rd October 2020) - Li, Lei; Guo, Haoran; Yao, Ge; Hu, Chenhui; Liu, Chunhong; Tian, Ziqi; Li, Baihai; Zhang, Qiuju; Chen, Liang
Abstract : Solar-driven reduction of CO2 into multi-carbon products plays a vital role in renewing CO2 utilization, while the key lies on screening efficient catalysts that possess moderate CO intermediate binding energy and eventually facilitate further C–C coupling to C2+ products. Abstract : Solar-driven reduction of CO2 into multi-carbon products plays a vital role in renewing CO2 utilization, while the key lies on screening efficient catalysts that possess moderate CO intermediate binding energy and eventually facilitate further C–C coupling to C2+ products. Herein, we proposed a synergistic coupling catalyst by anchoring the heteroatom B–Co dimer into porous C2 N (B–Co@C2 N) for photocatalytic CO2 reduction into ethane via applying first-principles calculations. The formation of the B–Co dimer can effectively modulate the Co-3d orbital toward lower energy levels, which weakens CO adsorption strength compared with Co–Co@C2 N and leads to a low C–C coupling energy barrier of ∼0.61 eV. The undesirable hydrogen evolution reaction is drastically suppressed due to the strong adsorption of the *CO2 /*COOH intermediate with positive limiting potential difference of U L (CO2 )– U L (H2 ). More importantly, the light absorbance of B–Co@C2 N is significantly enhanced in the visible and infrared light range compared with that of pure C2 N. The high binding energy combined with the AIMD simulations ensured structural stability and feasibility for future experimental synthesis. Our proposed synergy concept of single metal atom and nonmetal atom hybrids is expected to open a new avenue toward photocatalytic CO2 reduction into multi-carbon products under visible light.